Une approche sensible du son - Bertin, Raymond (Jeu : revue de théâtre, 2019)
Article sur l'artiste sonore Nancy Tobin.

A performer's perspective on three works for pianist and moving images : analysis with performance and practice strategies for Michel van der Aa's 'Transit', Nicole Lizée's 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby - Morano, Christopher (Université de Colombie-Britannique, 2017)
Interest in audio-visual works of art that are performed by a live pianist while integrating projected moving visual images has waxed and waned over a period of almost 300 years. The past twenty years or so has seen a re-emergence of this genre of classical music composition which places extra demands on the pianist performing these works. This dissertation explores the history of this genre, proposes a framework for analysis of these pieces, and examines from both analytical and performance perspectives three contrasting works for this medium: Michel van der Aa’s 'Transit', Nicole Lizée’s 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby. This research was

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Écritures chorégraphiques et sonores imbriquées : récits de collaborations avec Danièle Desnoyers - Tobin, Nancy (L’Annuaire théâtral : revue québécoise d’études théâtrales, 2016)
Ce texte revient sur le processus de création de trois spectacles chorégraphiques auxquels j’ai participé comme conceptrice sonore : Concerto grosso pour corps et surface métallique (1999), Duos pour corps et instruments (2003) et Là où je vis (2007). Ces parcours de recherche-création, traversés avec la chorégraphe Danièle Desnoyers (compagnie Le Carré des Lombes), permettent d’observer comment l’écriture sonore se développe in situ avec l’écriture chorégraphique. Les deux se forment ensemble en s’influençant l’une l’autre. Les trois spectacles choisis témoignent de différents modes de création de la matière sonore : amplification des danseurs, diffusion avec des haut-parleurs inusités, invention d’instruments et citation de musiques transformées. Les récits de collaborations qui suivent révèlent les manières dont la matière sonore a émergé de l’écriture chorégraphique et vice versa.

Layers of creativity in composition, rehearsal and performance: Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Tracking the Creative Process in Music Second International Conference, 2013)

Le son tactile ou la sensorialité excentrique dans les performances solos de Magali Babin - Abenavoli, Lorella (Circuit : musiques contemporaines, 2013)
How can the ephemeral touch of a caress become an aesthetic object? How can a fingernail scratching the mineral surface of a sheet of schist become music? How can intimate tactile experience become the scene of a collective artistic ritual? How does Magali Babin turn electronic sound into a medium for eccentric sensoriality? This article takes us into one region of Magali Babin’s artistic practice: the tactile world of sound that she uses in her solo performances. Author of a polymorphic sonic oeuvre, Magali Babin is a Quebec artist, performer, and composer whose artistic practice has incorporated sonic installations for the past two years. She is a key figure in Montreal’s alternative audio art, “edgy” improvisation, and experimental music scenes, moving freely among cutting-edge artistic categories.
Keywords: Magali Babin; art audio; art haptique; audio art; device; dispositif; eccentric sensoriality; electronic; haptic art; improvisation; performance sonore; sensorialité excentrique; sonic performance; électronique